Geopolitik indonesia menghadapi tantangan global: implementasi strategis dalam memperkuat pertahanan - Sulistyawati, Santi Maya (Maliki Interdisciplinary Journal, 2026)
This article discusses the role and implementation of Indonesian geopolitics in facing increasingly complex global dynamics. Geopolitics is understood as a multidimensional concept encompassing geographical, political, economic, legal, and security aspects, both at the national and international levels. Global geopolitical developments indicate a shift from a unipolar to a bipolar era, marked by the rise of new powers such as China and Russia, as well as the escalation of conflict in the Middle East. In Indonesia’s context, its strategic geographic position in the Asia-Pacific region presents the country with both significant opportunities and vulnerabilities to global power rivalries. Indonesia’s geopolitics is implemented through sustainable natural resource management, strengthening defense and security, infrastructure development, and international diplomacy. An adaptive and modern Nusantara Defense Strategy is one effort to maintain regional sovereignty amidst the complexity of regional threats. Furthermore, Pancasila serves as an ideological and moral foundation that guides the direction of Indonesian geopolitical policy, ensuring it remains oriented toward social justice, environmental sustainability, and world peace. Thus, this article emphasizes that Indonesian geopolitics serves not only as an instrument of defense and diplomacy but also as a comprehensive strategy to strengthen Indonesia’s position as an influential regional power while contributing to global stability.